2018
DOI: 10.12809/hkmj176808
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and tolerability of trastuzumab emtansine in advanced human epidermal growth factor receptor 2–positive breast cancer

Abstract: Introduction:The management of human epidermal growth factor receptor 2 (HER2)-positive breast cancer has changed dramatically with the introduction and widespread use of HER2-targeted therapies. There is, however, relatively limited real-world information about the effectiveness and safety of trastuzumab emtansine (T-DM1) in Hong Kong Chinese patients. We assessed the efficacy and toxicity profiles among local patients with HER2-positive advanced breast cancer who had received T-DM1 therapy in the second-line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…The T-DM1 benefit-risk profile in ELAINA is consistent with previous clinical trials ( 18 , 19 , 35 , 36 ) and real-world data in patients with pretreated LABC/mBC, including Chinese patients ( 37 - 41 ). A recent network meta-analysis suggested that pyrotinib plus capecitabine may be the most efficacious treatment among the nine regimens (including T-DM1) evaluated for patients with previously treated HER2-positive mBC ( 42 ).…”
Section: Discussionsupporting
confidence: 86%
“…The T-DM1 benefit-risk profile in ELAINA is consistent with previous clinical trials ( 18 , 19 , 35 , 36 ) and real-world data in patients with pretreated LABC/mBC, including Chinese patients ( 37 - 41 ). A recent network meta-analysis suggested that pyrotinib plus capecitabine may be the most efficacious treatment among the nine regimens (including T-DM1) evaluated for patients with previously treated HER2-positive mBC ( 42 ).…”
Section: Discussionsupporting
confidence: 86%
“…Furthermore, thrombocytopenia that developed in the first four T-DM1 cycles was predictive of a longer TTD in T-DM1 treatment. Thrombocytopenia has been identified as a characteristic of T-DM1 and as the most common grade ≥3 and dose-limiting adverse event in both clinical trials (10)(11)(12) and real-life studies (17,24,25). To the best of our knowledge, only two reports in the literature have studied the predictive value of thrombocytopenia during T-DM1 treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Limited data exist on T-DM1 effectiveness outside clinical trials. In a single-center retrospective study in Spain ( n = 15) and a five-center retrospective study in Hong Kong ( n = 37), median PFS was 10 and 6 months, respectively, and median OS was 34 months and not reached, respectively [ 10 , 11 ]. A retrospective observational multicenter study in Italy evaluated 250 patients treated with T-DM1, including those with pertuzumab pretreatment [ 12 ].…”
Section: Discussionmentioning
confidence: 99%